Anthropogenic impacts on the contamination of pharmaceuticals and personal care products (PPCPs) in the coastal environments of the Yellow and Bohai seas. (February 2020) - Yang, Lu; Zhou, Yunqiao; Shi, Bin; Meng, Jing; He, Bo; Yang, Hongfa; Yoon, Seo Joon; Kim, Taewoo; Kwon, Bong-Oh; Khim, Jong Seong; Wang, Tieyu
Graphical abstract: Highlights: Target 30 PPCPs were all detected in the coastal waters from the Yellow and Bohai seas. Established PPCI successfully explained the degree and sources of PPCPs contamination. Coastal contamination by PPCPs in Asia was at much higher pressure throughout the globe. OFL and ERY-H2 O posed relatively high risks towards algae, particularly in China. Abstract: Pharmaceuticals and personal care products (PPCPs) are recognized as one emerging group of environmental contaminants, capturing worldwide attention. These chemicals, closely connected to anthropogenic activities, are mainly transported through aquatic environments and reach coastal areas, eventually entering ocean offshore. Thus, this study concentrated on the 30 PPCPs in coastal waters of the Yellow and Bohai seas (77 sites), a fast-growing area with intensive anthropogenic activities. In general, the total concentrations of PPCPs in Chinese coastal waters (0.880–1194 ng L −1 ) greatly varied and were relatively greater than those (9.91–442 ng L −1 ) in Korean coastal waters. Sulfamethoxazole, sulfamethazine, oxytetracycline, ofloxacin, roxithromycin, anhydro-erythromycin, and caffeine were the seven predominant PPCPs in the coastal waters of study area. Further, we established the Predicted PPCPs Contamination Indicator (PPCI) to address potential anthropogenic activities being associated with site-specific PPCPs contamination. Three anthropogenic factors to PPCPs contamination were proven as the most influential, including (1) quantity of wastewater discharge, (2) gross product of meat, poultry, eggs and milk, and (3) gross aquatic product. The relatively high PPCI values appeared in Tianjin, Dalian, Tangshan, Yantai, and Qingdao in China and Gyeonggi and Jeonbuk in South Korea, which exhibited fairly good consistency with the corresponding PPCPs concentrations. A mini-review of the global PPCPs distributions revealed that seven priority PPCPs found in this study distributed widely in Asia rather than Europe, North America, and Australia. In general, global PPCPs contamination also reflected site- and region-specific distributions, suggesting varying usages and sources cross the region and/or country. Finally, the risk assessment suggested that ofloxacin and anhydro-erythromycin, with 36.4% and 23.4% sites higher than medium risks respectively, posed relatively high risks to sensitive algal species, Microcystis aeruginosa and Selenastrum capricornutum . Overall, the ecological risks of exposure of PPCPs in the Yellow and Bohai seas were higher compared to other regions of the world, thus the bilateral management of PPCPs between China and South Korea needs an immediate attention.